The night we lost him : a novel - Dave, Laura; OverDrive, Inc. (New York : MSR, Marysue Rucci Books, 2024)
"When the patriarch of a famed hotel empire dies under suspicious circumstances, his daughter and her estranged brother join forces to find out what happened, unraveling a larger mystery about who their father really was. From the author of the #1 New York Times bestseller and Reeses Book Club Pick The Last Thing He Told Me comes a riveting mystery wrapped in an epic love story"--
Electronic book.
Electronic reproduction.
Keywords: FICTION / Thrillers / Suspense; FICTION / Women; Advantage title -- Fiction; Novels; Electronic books; Thriller fiction